Patient-Reported Outcome Measures for Patients with Diabetes Mellitus Associated with Foot and Ankle Pathologies: A Systematic Review - Ortega-Ávila, Ana Belén; Cervera-Garvi, Pablo; Ramos-Petersen, Laura; Chicharro-Luna, Esther; Gijón-Noguerón, Gabriel (My University, 2019)
Background: Diabetes mellitus (DM) is a chronic and complex disease, which is a major cause of morbidity and mortality and affects all age groups. It commonly produces secondary effects on the foot, often making daily activities impossible. Patient-reported outcome measures (PROMs) provide a standardised method of obtaining patients’ outlooks on their functional status and wellbeing. Although many instruments have been proposed for obtaining data on persons with DM whose feet are affected by the disease, in many cases the psychometric properties of the instrument have yet to be established. The principal objective of our review was to identify PROMs specific for patients with DM affecting the foot and ankle and to evaluate the psychometric properties and methodological quality of these instruments. Methods: In this systematic review, we investigate studies (published in English or Spanish) based on the use of one or more PROMs specific to foot and ankle pathologies for patients with DM (type I or II). To do so, the databases PubMed, Scopus, CINAHL, PEDro and Google Scholar were searched for studies that analysed psychometric or clinimetric properties in this respect. These were assessed according to Terwee or COSMIN criteria. Results: Of the 1016 studies identified in the initial search, only 11 were finally included in the qualitative review. Analysis according to Terwee and COSMIN criteria showed that the Foot Health Status Questionnaire (FHSQ) presented the greatest number of positive values. Conclusions: The FHSQ is the highest-quality PROM currently available for the foot and ankle, for patients with DM.
Keywords: Diabetes - Complicaciones; Pie diabético - Cuidados de enfermería; Diabetes mellitus; Foot; Ankle; Psychometrics; Patient-reported outcome measures; Systematic Review